Comparisons of One to Three Monthly Injections of Aflibercept for Diabetic Macular Edema by Practical Protocol. (13th February 2021) - Hayashi, Yuko; Tatsumi, Tomoaki; Oshitari, Toshiyuki; Kaiho, Tomomi; Takatsuna, Yoko; Arai, Miyuki; Baba, Takayuki; Yamamoto, Shuichi
Abstract : The purpose of this study was to compare the efficacies of one initial intravitreal injection of aflibercept followed by a pro re nata (PRN; 1+PRN) regimen to those of three consecutive monthly injections followed by the PRN (3+PRN) regimen for diabetic macular edema (DME) with practical protocols. The medical records of 95 eyes of 71 cases that were diagnosed with DME and had received intravitreal aflibercept (IVA) injections were reviewed. Fifty-seven eyes had received IVA with the 1+PRN regimen, and 38 eyes had received IVA with the 3+PRN regimen. The best-corrected visual acuity (BCVA) and the central macular thickness (CMT) were measured at the baseline and at 1, 3, 6, and 12 months after the IVA. The mean number of injections of the 1+PRN group was 2.9 ± 1.7, which was significantly fewer than that of the 3+PRN group at 4.6 ± 1.4 (P < 0.001 ). The change of the mean BCVA before and after the IVA at 12 months of the 3+PRN group was − 0.14 ± 0.17 logMAR units which was significantly better than that of the 1+PRN group of − 0.045 ± 0.25 logMAR units (P = 0.02 ). The change of the CMT before and after the IVA at 6 months of the 3+PRN group was − 141.3 ± 152.4   μ m which was significantly more than that of the 1+PRN group at − 86.1 ± 117.8   μ m (P = 0.013 ). Although the mean number of injections was more than that in the 1+PRN regimen, the 3+PRN regimen had better visual outcomes at 12 months. In a practical protocol, we recommend the 3+PRN regimen for patients with DME (IRB#3541).